A Bibliometric Analysis and Visualisation of Research Trends in Orthopaedic Implants - Singh , Bhupinder (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Several metals are used for orthopaedic implants. The bibliometric analysis had been conducted to understand the active authors, organizations, journals, and countries involved in the research domain of “orthopaedic implants”. All published articles related to “orthopaedic implants” from “Scopus”, were analyzed using the VOS viewer to develop analysis tables and visualization maps. This article had set the objective to consolidate the scientific literature regarding “orthopaedic implants” and also to find out the trends related to the same. The most active journals in this research domain were the Biomaterials. The most active country was the United States of America. The leading organization engaged in research regarding Orthopaedic implants was the IRCCS Rizzoli Orthopaedic Institute, Bologna of Italy. The most active authors who had made valuable contributions related to dental implants were Arciola C.R and Webster T.J.